Osteocranium of Tor tambroides (Cypriniformes: Cyprinidae) from Tangse River, Aceh, Indonesia - YUSRIZAL AKMAL; ilham zulfahmi; YENI DHAMAYANTI; EPA PAUJIAH (Society for Indonesian Biodiversity, 2020)
Abstract. Akmal Y, Zulfahmi I, Dhamayanti Y, Paujiah E. 2020. Osteocranium of Tor tambroides (Cypriniformes: Cyprinidae) from Tangse River, Aceh, Indonesia. Biodiversitas 21: 442-450. We report the first detailed descriptive osteocranium of keureling, Tor tambroides (Cypriniformes: Cyprinidae) collected from Tangse River, Indonesia. This study aimed to describe the cranium morphology of keureling (Tor tambroides). Keureling fish used in this study were obtained from the catch of fishers in the Tangse River, District of Pidie, Aceh Province, Indonesia. Stages of research include sample preparation, bone preparations, and identification of cranium nomenclature. For osteological examination, the cranium of the keureling prepared physically and chemically. Based on the results, the cranium of the keureling is divided into two major parts, namely the neurocranium and the facial bone,s including the branchial apparatus. The neurocranium is divided into (anterior to posterior) olfactory (ethmoid), orbital, otic, and occipital regions while the rest divided into oromandibular, opercular series, branchial arch, mandibular arch, and hyoid arch (suspensorium) regions. The neurocranium includes bones in the dermal series of the skull and endochondral bones protecting the brain. At the same time, branchiocranium are those located in the oromandibular part, opercular series, and branchial arch.